2023
DOI: 10.3390/ma16031013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tribological Adaptation Controlled by Tribosynthesis of FeWO4 on an WC-Reinforced Electron Beam M2 Steel Coating Rubbed against a HSS Disk in a Range of Sliding Speeds

Abstract: In the present work, the tribological experiments on sliding the electron beam composite M2+WC coating have been carried out with characterization of the sample microstructures and phases both before and after the testing using metallography, SEM, EDS, and XRD. The sliding in the speed range 0.8–3.6 m/s resulted in simultaneous reduction in both wear rate and coefficient of friction with the sliding speed. Investigations showed that such a tribological adaptation was due to the tribochemical generation of lubr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…Tribological experiments on sliding the electron beam composite M2 + WC coating have been carried out in the sliding speed range 0.8-3.6 m/s that resulted in simultaneous reduction in both wear rate and coefficient of friction [23]. It was demonstrated that such a finding was due to tribological adaptation driven by the tribochemical generation of lubricating FeWO 4 and Fe 2 WO 6 mixed oxides on the worn surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Tribological experiments on sliding the electron beam composite M2 + WC coating have been carried out in the sliding speed range 0.8-3.6 m/s that resulted in simultaneous reduction in both wear rate and coefficient of friction [23]. It was demonstrated that such a finding was due to tribological adaptation driven by the tribochemical generation of lubricating FeWO 4 and Fe 2 WO 6 mixed oxides on the worn surfaces.…”
Section: Introductionmentioning
confidence: 99%